Evaluation of AlGaN/GaN metal–oxide–semicondutor high-electron mobility transistors with plasma-enhanced atomic layer deposition HfO2/AlN date dielectric for RF power applications. (24th August 2017) - Chiu, Yu Sheng; Luc, Quang Ho; Lin, Yueh Chin; Huang, Jui Chien; Dee, Chang Fu; Majlis, Burhanuddin Yeop; Chang, Edward Yi
Abstract: A plasma enhanced atomic layer deposition (PEALD) HfO2 /AlN dielectric stack was used as the gate dielectric for AlGaN/GaN metal–oxide–semiconductor high-electron-mobility transistors (MOS-HEMTs) for high-frequency power device applications. The capacitance–voltage ( C – V ) curves of the HfO2 /AlN/GaN MOS capacitor (MOSCAP) showed a small frequency dispersion along with a very small hysteresis (∼50 mV). Moreover, the interface trap density ( D it ) was calculated to be 2.7 × 10 11 cm −2 V −1 s −1 at 150 °C. Using PEALD-AlN as the interfacial passivation layer (IPL), the drain current of the HfO2 /AlN MOS-HEMTs increased by about 46% and the gate leakage current decreased by six orders of magnitude as compared with those of the conventional Schottky gate AlGaN/GaN HEMTs processed using the same epitaxial wafer. The 0.3-µm-gate-length HfO2 /AlN/AlGaN/GaN MOS-HEMTs demonstrated a 2.88 W/mm output power, a 23 dB power gain, a 30.2% power-added efficiency at 2.4 GHz, and an improved device linearity as compared with the conventional AlGaN/GaN HEMTs. The third-order intercept point at the output (OIP3) of the MOS-HEMTs was 28.4 as compared with that of 26.5 for the conventional GaN HEMTs. Overall, the MOS-HEMTs with a HfO2 /AlN gate stack showed good potential for high-linearity RF power device applications.